Dora Emilia Mora de Retana, a remembrance - Atwood, John T. (2016)
It was with severe regrets that I learned of the untimely death of Dora Emilia Mora de Retana. In 1985 while completing the Orchidaceae for Flora of La Selva Biological Station, I started a search for a Costa Rican with whom to collaborate on a larger project.